- Gambaran Pengetahuan Dan Sikap Tentang Donor Darah Mahasiswa Asrama Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta - Teti Wulandari (Jurnal Ilmiah Cerebral Medika, 2023)
Background: Blood donation is an activity of donating blood for transfusion purposes, the number of voluntary blood donors in Indonesia is around 20% of the total production of blood bags per year, the rest is met by replacement donors. Students are part of the community who can donate blood, the lack of knowledge about blood donation results in low blood donation among students.Objectives: The objective of this study to describe knowledge and attitudes about blood donors at the dormitory students at the Faculty of Health, Jenderal Achmad Yani yogyakartaUniversity, Yogyakarta.Method: This study uses a quantitative descriptive, data collection using a questionnaire. The sample in this study were residents of the Jenderal Achmad Yani Yogyakarta University dormitory in Yogyakarta with an accidental sampling technique of 66 students.Results: The results of the study showed that the knowledge of blood donors in the good category was 16 (24.24%), the sufficient category was 33 (50.00%), the poor category was 17 (25.76%). While attitudes about blood donors with a positive category 34 (51.52%), and a negative category 32 (48.48%).Conclusion: The results majority of the dormitory students at the Faculty of Health, Jenderal Achmad Yani University Yogyakarta, have sufficient knowledge about blood donation, and the attitude of the dormitory students has a positive attitude.